Relationship between Adversity Intelligence, Communication Skills and Digital Literacy with Biology Learning Outcomes of State High School Students in Enrekang Regency - Arma; Nurhayati B; Muh. Junda; Firdaus Daud; Arsad Bahri (Jurnal Penelitian Pendidikan IPA, 2025)
This study was motivated by the low learning outcomes of biology phase E students of State High Schools in Enrekang Regency. This study aims to analyze the relationship between adversity intelligence, communication skills, and digital literacy with biology learning outcomes. Using quantitative methods of ex post facto type.  The population was 1205 phase E students with a sample of 300 students selected by proportional random sampling. Data were collected using a Likert scale questionnaire and multiplechoice tests and the data were analyzed using regression analysis. The results of the analysis show that adversity intelligence has a significant relationship to learning outcomes with a sig value of 0.000 < 0.05 and a contribution of 30%; communication skills have a significant relationship to learning outcomes with a sig value of 0.000 < 0.05 and a contribution of 19.9%; digital literacy has a significant relationship to learning outcomes with a sig value of 0.000 < 0.05 and a contribution of 18.5%; adversity intelligence variables, communication skills and digital literacy together have a significant relationship to biology learning outcomes with a sig value of 0.000 < 0.05 and a contribution of 37.8%.